inclusion of students with disabilities in public schools of a city of the interior of Ceará: The view of school managers - Souza, Maria Neurismar Araújo de; Almeida, Maria Iranilda Meneses; Soares, Stela Lopes (Revista Hipótese, 2023)
Social inclusion is a means and a fundamental factor for the development and equity of the Brazilian nation. The objective of this study was to analyze the view of school managers in a municipality in the interior of Ceará about the inclusion process of students with disabilities. This study is exploratory, descriptive, and with a qualitative approach, being carried out from August to November 2022, having as research field three public schools in the municipality of elementary school. Data collection was performed through interviews. The research had the participation of 4 school managers, who signed a Free and Informed Consent Form agreeing to participate in the study. It can be highlighted that in the chosen institutions, students with disabilities have already been inserted in their scope; therefore, these characteristics strengthen experiences closer to the expectations deposited in the school. After data analysis, we can conclude through research with the participating school managers that there is a low number of students with disabilities in the schools evaluated, and this result provokes the reflection of whether there would be other people with school-age disabilities who could be included and studying in these institutions, a fact that deserves to be investigated in other studies.
Keywords: Inclusion; School; Student with disabilities